2015
DOI: 10.1155/2015/918602
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making for Third Party Logistics Supplier Selection in Semiconductor Manufacturing Industry: A Nonadditive Fuzzy Integral Approach

Abstract: The semiconductor industry has a unique vertically disintegrated structure that consists of various firms specializing in a narrow range of the value chain. To ensure manufacturing and logistics efficiency, the semiconductor manufacturers considerably rely on 3PL suppliers to achieve supply chain excellence. However, 3PL supplier selection is a complex decision-making process involving multiple selection criteria. The goal of this paper is to identify the key 3PL selection criteria by employing the nonadditive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Akman and Baynal [2] combined FAHP and fuzzy TOPSIS to determine the best 3PL provider among seven alternatives for a Turkish tyre company. Hwang and Shen [23] proposed a non-additive fuzzy integral to identify criteria weights and select the best 3PL provider. The six main criteria they considered were information technology, cost, service, performance, quality assurance, and intangibles.…”
Section: Literature Review Related To Third-party Logistics Provider Evaluationmentioning
confidence: 99%
“…Akman and Baynal [2] combined FAHP and fuzzy TOPSIS to determine the best 3PL provider among seven alternatives for a Turkish tyre company. Hwang and Shen [23] proposed a non-additive fuzzy integral to identify criteria weights and select the best 3PL provider. The six main criteria they considered were information technology, cost, service, performance, quality assurance, and intangibles.…”
Section: Literature Review Related To Third-party Logistics Provider Evaluationmentioning
confidence: 99%
“…The AHP program is flexible enough to incorporate both qualitative and quantitative factors. In [22], AHP method was applied to classify hightech manufacturers in Taiwan according to the importance of selection criteria, and it was found that the three criteria groups with the greatest influence on selection are performance, cost and service. Sensitivity analysis helps decision-makers see the effect of potential data changes and/or miscalculations on their pairwise comparisons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, the evaluation of 3PL specialists signifies the subjective criteria for tire fabricating industry [55]. Additionally, affectability examination for checking the overall significance of 3PL administration criteria does not appear in this methodology [141].…”
Section: Lead Logistics Providersmentioning
confidence: 99%